Pulmonary embolism in childhood – 10-year single center experience - E. Levunlieva; R. Lekova; K. Nenova; L. Dimitrov; D. Pechilkov; A. Kaneva (Българска кардиология)
Pulmonary embolism (PE) is a disease representing partial or complete obstruction by various types of emboli of one or more of the pulmonary bed vessels. It is relatively rare in childhood, but in recent years it is found more often in children. The aim of the study was to perform a retrospective analysis of age distribution, predisposing factors, clinical presentation, and manage-ment in children with proven PE not directly related to cardiac surgery over a 10-year period. Data of 14 children with a total of 15 episodes of pulmonary thromboembolism (PTE), hospitalized in the Clinic of Pediatric Cardiology, National Heart Hospital, Sofia, Bulgaria with evidence of pulmonary embolism for a period of 10 years were analysed. The children with PTE are 7 girls and 7 boys, aged 3 months to 17.5 years. In two of the cases (13%), PTE occurred under the age of 3 years, in 5 cases (33%) between the ages of 6 and 13 years, and in 8 (53%) between the ages of 13 and 18 years. The clinical manifestations included: tachypnea and dyspnea – 73% (n = 11), chest pain – 73% (n = 11), tachycardia – 67% (n = 10), asthenia/fatigue – 60% (n = 9), hypoxemia (SatO2 < 95%) – 53% (n = 8), hemoptysis – 13% (n = 2), acute hemodynamic collapse – 7% (n = 1). In the acute phase of the disease, the patients were treated using unfractionated heparin, low molecular weight heparin, interventional treatment with thromboaspiration and local fibrinolysis, as well as systemic fibrinolysis. The increasing incidence and the severity of the disease require a good knowledge of risk factors and symptoms, as well as the development of age-specific recommendations for diagnosis, management, and follow-up of the disease.